Applied Promotion Technology in CV Bintang Abadi to Advance and Improve Tecnopreurship Batik Products Klampar - Aryo Bayu Wibisono; Aphief Tri Artanto; Heru Subiyantoro (Future Science)
Batik is one of the superior products in Indonesia, Batik products stretching from Sabang to Merauke. The famous batik product in Indonesia is Madura Batik, which has special characteristics in Indonesia. CV Bintang Abadi which houses several batik makers in Batik Klampar Village, Kec. Proppo, Kab. Pamekasan has advantages in terms of color and batik design. As revealed in previous studies, if the advantage is believed to be hereditary from families who had previously pursued Batik. Besides Batik Klampar has the advantage of products that can be proud of in the District. Pamekasan because it is quite well known in Madura. The problem of CV Bintang Abadi which houses several Batik Klampar crafters is that they do not yet know the brand, and do not know how to reach markets outside the city of Pamekasan. As a result, in CV Bintang Abadi in particular, and Batik centers in Klampar Village in general are mostly marketed by other parties with different names, besides that Batik Klampar center products become less developed because they only become producers that sell in the Pamekasan region with competitors in the Klampar batik alone and are less well schemed with managerial product marketing. Through the service of the RISMI scheme, it is hoped that there will be a tactical scheme to support and improve the rule model of the communication strategy of the CV Bintang Abadi promotion which houses several Batik Klampar Villages through applied technology production in the form of Android Applications, and Online Marketing as a result of previous research. Applied service with the RISMI scheme will be carried out in Klampar Village, Proppo District, and Pamekasan Regency. This service will not only implement technology, but there will be an approach related to the business assistance of Batik Klampar products involving DKV and Architecture Study Programs and Students in both study programs